Usefulness of autocidal gravid ovitraps for the surveillance and control of Aedes (Stegomyia) aegypti (Diptera: Culicidae) in eastern Colombia (2020)
In the past decade, new strategies have been developed to control the Aedes aegypti (Diptera: Culicidae) mosquito vector, as well as a broad range of arboviral agents. Vector control surveillance programmes in Puerto Rico and Australia have implemented the Centers for Disease Control and Prevention autocidal gravid ovitrap (AGO), which has had an impact on vector density and, consequently, the epidemiology of arboviral infections. Colombia intends to establish the AGO as a new tool for the surveillance and control of the A. aegypti vector. AGOs were evaluated in a hyperendemic area for dengue virus during an 8-week period in Villavicencio city, eastern Colombia. The results indicated that the AGOs detect a high density of A. aegypti, with positive results for these traps of over 80% and an average catch of six individuals per trap per week. Acceptance of AGOs in the community exceeded 95%, and adherence was around 89%. This study's results demonstrate, for the first time in Colombia, that traps are a useful tool for the surveillance of A. aegypti. Future studies must consider the implementation of AGOs in the region. © 2020 The Royal Entomological Society